Effect of Intercurrent Infections and Vaccinations on Immune and Inflammatory Biomarkers Among Human Immunodeficiency Virus-Infected Adults on Suppressive Antiretroviral Therapy - Tan, Darrell H. S. (Open Forum Infect Dis, 2015)
We used generalized estimating equations to quantify the impact of recent vaccination or intercurrent infections on immune and inflammatory biomarkers among 144 human immunodeficiency virus (HIV)-infected adults with HIV RNA < 50 copies/mL on antiretroviral therapy. These events were associated with a 2.244 µg/mL increase in high sensitivity C-reactive protein and should be routinely assessed in future studies.